Isoliquiritigenin as a modulator of the Nrf2 signaling pathway: potential therapeutic implications - Qiu, Mangmang; Ma, Kang; Zhang, Junfeng; Zhao, Zhaohua; Wang, Shan; Wang, Qing; Xu, Hao (Frontiers in Pharmacology, 2024)
Nuclear factor erythroid-2-related factor 2 (Nrf2), a transcription factor responsible for cytoprotection, plays a crucial role in regulating the expression of numerous antioxidant genes, thereby reducing reactive oxygen species (ROS) levels and safeguarding cells against oxidative stress. Extensive research has demonstrated the involvement of Nrf2 in various diseases, prompting the exploration of Nrf2 activation as a potential therapeutic approach for a variety of diseases. Consequently, there has been a surge of interest in investigating the Nrf2 signaling pathway and developing compounds that can modulate its activity. Isoliquiritigenin (ISL) (PubChem CID:638278) exhibits a diverse range of pharmacological activities, including antioxidant, anticancer, and anti-tumor properties.Notably, its robust antioxidant activity has garnered significant attention. Furthermore, ISL has been found to possess therapeutic effects on various diseases, such as diabetes, cardiovascular diseases, kidney diseases, and cancer, through the activation of the Nrf2 pathway. This review aims to evaluate the potential of ISL in modulating the Nrf2 signaling pathway and summarize the role of ISL in diverse diseases prevention and treatment through modulating the Nrf2 signaling pathway.